a) 2a + (4a - 3b + 5c) + (5c - 2b) = 2a+4a-3b+5c+5c-2b = 6a-5b+10c
b) 5x + 3y + (2y - 4z) - (5y + 6z) = 5x+3y+2y-4z-5y-6z = 5x-10z
c) -3r - (2r - 4s - t) - (6r + 5s) = -3r-2r+4s+t-6r-5s = -11r-s+t
d) 4k - (2m + n) - (-k - m) + (3m - n) = 4k-2m-n+k+m+3m-n = 5k+2m-2n
e) 7a - (a + b + ab) + (2a - 3ab) = 7a-a-b-ab+2a-3ab = 8a-b-4ab
f) 4xy + (-2x - 3y) - (-5x + y - 5xy) = 4xy-2x-3y+5x-y+5xy = 3x-4y+9xy
g) 6m - (2m² + n) + (3m - 2n - 5m²) = 6m-2m²-n+3m-2n-5m² = 9m-3n-7m²
h) -2t - (3t - t²) - (5s + 4t) - (2t² - s) = -2t-3t+t²-5s-4t-2t²+s = -4s-9t-t²
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
a) 2a + (4a - 3b + 5c) + (5c - 2b) = 2a+4a-3b+5c+5c-2b = 6a-5b+10c
b) 5x + 3y + (2y - 4z) - (5y + 6z) = 5x+3y+2y-4z-5y-6z = 5x-10z
c) -3r - (2r - 4s - t) - (6r + 5s) = -3r-2r+4s+t-6r-5s = -11r-s+t
d) 4k - (2m + n) - (-k - m) + (3m - n) = 4k-2m-n+k+m+3m-n = 5k+2m-2n
e) 7a - (a + b + ab) + (2a - 3ab) = 7a-a-b-ab+2a-3ab = 8a-b-4ab
f) 4xy + (-2x - 3y) - (-5x + y - 5xy) = 4xy-2x-3y+5x-y+5xy = 3x-4y+9xy
g) 6m - (2m² + n) + (3m - 2n - 5m²) = 6m-2m²-n+3m-2n-5m² = 9m-3n-7m²
h) -2t - (3t - t²) - (5s + 4t) - (2t² - s) = -2t-3t+t²-5s-4t-2t²+s = -4s-9t-t²